2018
DOI: 10.4018/978-1-5225-3710-6.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Women's Economic Empowerment Through Entrepreneurship in Saudi Arabia

Abstract: This chapter aims, first, to explore the state of the art of women's economic empowerment as a challenging research inquiry that needs a real investigation and to explore the different mechanisms of entrepreneurship development for women. It presents, then, the evidence of how Saudi women are economically empowered and how their potential is unleashed and sparked through entrepreneurship mechanisms. This chapter is based on a literature review on women's economic empowerment and entrepreneurship and a desk res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Women's entrepreneurship offers governments the potential to optimize economic growth and use available resources (Faisal et al, 2017;Ennis, 2019). With a growing population dependent on the social welfare system, a greater receptivity to private enterprises can lessen pressures on the government while supporting economic growth (Aloulou, 2018;Tok, 2020). For women in emerging economies, there is also evidence of entrepreneurship directly Women's entrepreneurship in the GCC impacting poverty alleviation in low-income countries (Palali c et al, 2020) as lower educational levels, coupled with socio-cultural constraints, make women a particularly disadvantaged group.…”
Section: Entrepreneurship Promotion In the Gulf Cooperation Councilmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's entrepreneurship offers governments the potential to optimize economic growth and use available resources (Faisal et al, 2017;Ennis, 2019). With a growing population dependent on the social welfare system, a greater receptivity to private enterprises can lessen pressures on the government while supporting economic growth (Aloulou, 2018;Tok, 2020). For women in emerging economies, there is also evidence of entrepreneurship directly Women's entrepreneurship in the GCC impacting poverty alleviation in low-income countries (Palali c et al, 2020) as lower educational levels, coupled with socio-cultural constraints, make women a particularly disadvantaged group.…”
Section: Entrepreneurship Promotion In the Gulf Cooperation Councilmentioning
confidence: 99%
“…Researchers have shown that women's entrepreneurship empowers them, improves social life (Itani et al , 2011; Aloulou, 2018; Debnath et al , 2020; Pachorkar et al , 2020) and enhances self-confidence (Danish and Smith, 2012) and financial independence, which, in turn, would place women in a position of power to influence family decisions (Alexandre and Kharabsheh, 2019). Moreover, many researchers have demonstrated the impact the empowered women entrepreneurs can have on women around them, for example, by hiring other female workers (Alkhaled, 2021).…”
Section: Negotiating a Place For Women – Empowerment And Digital Spacesmentioning
confidence: 99%
“…Other researchers such as Wassim, (2017) aimed to explore the state of the art of women's economic empowerment as a challenging research inquiry that needs a realistic investigation and explores the different mechanisms of entrepreneurship development for Women. It presents the evidence of how Saudi women are economically empowered and how their potentials are unleashed sparked through entrepreneurship training and education programs; the incubation of their entrepreneurial and creative businesses, the building of their business networking, the deployment of Information and Communication Technology (ICT) and social media for their potentials and competencies, and the corporate social responsibility, funding and community programs.…”
Section: Literature Reviewmentioning
confidence: 99%